ANALISIS FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MATA PELAJARAN IPS DI SMP NEGERI SEKECAMATAN ALALAK KABUPATEN BARITO KUALA - Noor Hidayah (JURNAL SOCIUS, 2017)
The aim of research to analyze the factors that affect the learning achievement with a quantitative approach. This type of research is a kind of field research (field research) with quantitative approach. The field research is a study to obtain the correct data in the field. So this research is quantitative research that is not only to obtain the data, but also to prove the existence of the effect of parental education and economic status of families with student achievement in social studies SMP se Alalak districts.Test results obtained by the value of R F or the value of the correlation coefficient of 0.901. This value can be interpreted that the relationship of education, economic status of parents, families and schools on student achievement considered strong. The result of the value of F (246.413)> F table (2.37), and sig. Smaller than the probability value 0.05 or value 0.000 <0.05. So P-value <α = 0.05, then Ho is rejected and Ha accepted.Thus the high and low achievement (based on the value of report cards) students of SMP Negeri se Alalak districts affected by the level of education, economic status of parents, families and school students. Parents guide their children is more important in the home in order to be motivated to learn in addition, it also did not escape the role of family support so that his diligent study and school. So is the teacher's role is very important role in educating (as second parents) and taught to students in the school. Schools as the main spearhead forward whether or not the next generation naturally always follow the development of educational progress.Keywords: Factor analysis, Achievement, IPSTujuan penelitian untuk menganalisa faktor yang mempengaruhi prestasi belajar dengan pendekatan kuantitatif. Jenis penelitian adalah jenis penelitian lapangan (field research) dengan pendekatan kuantitatif. Penelitian lapangan merupakan suatu penelitian untuk  memperoleh data yang benar terjadi di lapangan. Jadi penelitian ini adalah penelitian kuantitatif  yang tidak  sekedar untuk memperoleh data, akan tetapi juga untuk membuktikan ada tidaknya pengaruh tingkat pendidikan orang tua dan status ekonomi keluarga dengan prestasi belajar siswa mata pelajaran IPS di SMP Negeri se kecamatan Alalak.Hasil Uji F diperoleh nilai R atau nilai koefisien korelasi sebesar 0,901. Nilai ini dapat diartikan bahwa hubungan pendidikan, status ekonomi orang tua, keluarga dan sekolah terhadap prestasi belajar siswa dikategorikan kuat. Hasil nilai Fhitung (246,413) > Ftabel (2,37), dan nilai sig. Lebih kecil dari nilai probabilitas 0,05 atau nilai 0,000 < 0,05.  Jadi  P-value < α = 0,05 maka Ho ditolak dan Ha diterima.Dengan demikian tinggi rendahnya prestasi belajar (berdasarkan nilai hasil raport) siswa SMP Negeri se kecamatan Alalak dipengaruhi oleh tingkat pendidikan, status ekonomi orang tua, keluarga dan sekolah siswa. Orang tua yang lebih utama membimbing anaknya di rumah agar termotivasi untuk belajar di samping itu juga tidak lepas peran keluarga yang mendukung agar anaknya rajin belajar dan sekolah. Begitu juga peran  guru sangatlah penting perannya dalam mendidik (sebagai orang tua kedua) dan mengajar bagi siswa di sekolah. Sekolah sebagai ujung tombak utama maju tidaknya generasi penerus bangsa sudah sewajarnya selalu mengikuti perkembangan kemajuan pendidikan.Kata Kunci : Analisis Faktor, Prestasi Belajar, IPS